2010
DOI: 10.1371/journal.pone.0013732
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb CBX7 Directly Controls Trimethylation of Histone H3 at Lysine 9 at the p16 Locus

Abstract: BackgroundH3K9 trimethylation (H3K9me3) and binding of PcG repressor complex-1 (PRC1) may play crucial roles in the epigenetic silencing of the p16 gene. However, the mechanism of the initiation of this trimethylation is unknown.Methodology/Principal FindingsIn the present study, we found that upregulating the expression of PRC1 component Cbx7 in gastric cancer cell lines MGC803 and BGC823 led to significantly suppress the expression of genes within the p16-Arf-p15 locus. H3K9me3 formation was observed at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 33 publications
2
48
0
Order By: Relevance
“…We also cannot exclude the hypothesis that the shRNA constructs used in the previous studies may have interfered with the expression of other genes, maybe of the Pc family. The behavior of MEFs derived from Cbx7-KO mice and Cbx7-overexpressing transgenic mice described herein is supported by the drastic downregulation of CBX7 expression previously reported by several groups in malignant neoplasias -including thyroid (6), pancreatic (8), colon (11), lung (present study), gastric (10), bladder (7), and breast (9) carcinomas -and by a reduced growth rate achieved by restoration of CBX7 expression in carcinoma cells of different origin (6,9,11,38).…”
Section: Discussionsupporting
confidence: 85%
“…We also cannot exclude the hypothesis that the shRNA constructs used in the previous studies may have interfered with the expression of other genes, maybe of the Pc family. The behavior of MEFs derived from Cbx7-KO mice and Cbx7-overexpressing transgenic mice described herein is supported by the drastic downregulation of CBX7 expression previously reported by several groups in malignant neoplasias -including thyroid (6), pancreatic (8), colon (11), lung (present study), gastric (10), bladder (7), and breast (9) carcinomas -and by a reduced growth rate achieved by restoration of CBX7 expression in carcinoma cells of different origin (6,9,11,38).…”
Section: Discussionsupporting
confidence: 85%
“…Polycomb group (PcG) proteins and other factors play important roles in the regulation of p16 expression (Gil and Peters, 2006;Deng et al, 2010;Li et al, 2010). In the 293T cells transiently transfected with p16ATF-6I, we found that the transcription level of the p16 activator Ets2 gene was slightly increased and that of the repressor Suz12 gene was significantly decreased.…”
Section: Discussionmentioning
confidence: 96%
“…ChIP assays were performed and analyzed essentially as described (Shang et al, 2000;Li et al, 2010). The antibodies used were rabbit anti-trimethylated H3K4 (H3K4me3; no.…”
Section: Chromatin Immunoprecipitation (Chip) Assaymentioning
confidence: 99%
“…However, various mechanisms may influence ARF and p27 KIP1 up-regulation during senescence. For instance, ARF can be restored by the removal of the Polycomb genes BMI1 and CBX7 (28,29), and p27 KIP1 can be degraded by the E3 ligase Skp2 (30). Rb has a nonredundant role in senescent cells by mediating heterochromatin formation at E2F1 targets.…”
Section: Discussionmentioning
confidence: 99%